Eosinophils as a predictive marker of treatment-related adverse events in mRCC patients treated with first-line immune-checkpoint inhibitor combination therapy - Tatsushi Kawada; Satoshi Katayama; Takafumi Yanagisawa; Keiichiro Mori; Wataru Fukuokaya; Kazumasa Komura; Takuya Tsujino; Ryoichi Maenosono; Kiyoshi Takahara; Takuhisa Nukaya; Lan Inoki; Shingo Toyoda; et al. (Scientific Reports)
Abstract Immune checkpoint inhibitors (ICIs) are a key component of first-line treatment for metastatic renal cell carcinoma (mRCC). However, predicting treatment-related adverse events (TRAEs) remains challenging. This study investigated the utility of eosinophil-related biomarkers as predictors of Common Terminology Criteria for Adverse Events grade ≥ 3 TRAEs in mRCC patients undergoing ICI combination therapy. In this retrospective analysis across 21 hospitals in Japan, we examined 180 patients treated with ICI/ICI therapy and 216 patients treated with ICI/tyrosine kinase inhibitor (TKI) therapy. Grade ≥ 3 TRAEs occurred in 39.4% and 31.9% of patients in the ICI/ICI and ICI/TKI groups, respectively. An elevated eosinophil proportion of ≥ 2.0% (odds ratio [OR]: 2.36; 95% CI [confidence interval] 1.23–4.54, p = 0.01) and a low neutrophil/eosinophil ratio (NER) of ≤ 40.0 (OR: 2.78, 95% CI 1.39–5.53, p = 0.004) were significant predictors of severe TRAEs in the ICI/ICI group. However, no significant associations were found in the ICI/TKI group. These findings may help identify patients who suffer from grade ≥ 3 TRAEs and help determine individualized treatment strategies in patients with mRCC.